2012
DOI: 10.1093/infdis/jis505
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of MyD88 and TRIF in Hematopoietic and Resident Cells During Murine Gram-Negative Pneumonia

Abstract: MyD88- and TRIF-dependent signaling has a differential contribution to host defense in different cell types that changes from early- to late-stage gram-negative pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 28 publications
5
34
1
Order By: Relevance
“…As with many bacterial infections, MyD88 plays a more significant role than TRIF (170,173,174). Furthermore, the protective role of MyD88 during infection seems to be mediated through expression in both bone-marrow-derived cells and non-bone-marrow-de-rived cells, while that of TRIF is mediated through expression in bone-marrow-derived cells only (175). Mice with defective TLR4 signaling have higher K. pneumoniae CFU and greater mortality during K. pneumoniae pneumonia, indicating that TLR4 prevents mouse mortality and high bacterial loads (176)(177)(178).…”
Section: K Pneumoniae and Host Immune Defensesmentioning
confidence: 99%
“…As with many bacterial infections, MyD88 plays a more significant role than TRIF (170,173,174). Furthermore, the protective role of MyD88 during infection seems to be mediated through expression in both bone-marrow-derived cells and non-bone-marrow-de-rived cells, while that of TRIF is mediated through expression in bone-marrow-derived cells only (175). Mice with defective TLR4 signaling have higher K. pneumoniae CFU and greater mortality during K. pneumoniae pneumonia, indicating that TLR4 prevents mouse mortality and high bacterial loads (176)(177)(178).…”
Section: K Pneumoniae and Host Immune Defensesmentioning
confidence: 99%
“…In our previous studies on the role of TRIF during K. pneumoniae airway infection, we demonstrated that TRIF mutant mice have an impaired antibacterial defense, illustrated by a significantly higher bacterial load in the lungs, blood and spleen [8] . In these investigations, we also observed higher bacterial loads in the livers of TRIF mutant mice and TRIF bone marrow chimeras lacking TRIF in hematopoietic cells (online suppl.…”
Section: Ifn-γ Production Is Impaired In Trif Mutant Mice During Klebmentioning
confidence: 88%
“…Animals TRIF mutant mice, generated on a C57Bl/6 genetic background [22] [8,9] . The mice were sacrificed at the indicated time points after infection and their organs were harvested and processed exactly as described [8,25] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations